Tensor Product of Product Vectors
📂Linear Algebra Tensor Product of Product Vectors Buildup Let’s denote the set of functions from the finite set Γ \Gamma Γ to the complex number space as indicated by C Γ \mathbb{C}^{\Gamma} C Γ .
C Γ = { f : Γ → C }
\mathbb{C}^{\Gamma} = \left\{ f : \Gamma \to \mathbb{C} \right\}
C Γ = { f : Γ → C }
When Γ = n = { 1 , … , n } \Gamma = \mathbf{n} = \left\{ 1, \dots, n \right\} Γ = n = { 1 , … , n } , it essentially becomes C n = C n \mathbb{C}^{\mathbf{n}} = \mathbb{C}^{n} C n = C n , and the tensor product of vector spaces is defined as follows.
C Γ 1 ⊗ C Γ 2 : = C Γ 1 × Γ 2
\mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}} := \mathbb{C}^{\Gamma_{1} \times \Gamma_{2}}
C Γ 1 ⊗ C Γ 2 := C Γ 1 × Γ 2
Assuming v i ∈ C Γ i v_{i} \in \mathbb{C}^{\Gamma_{i}} v i ∈ C Γ i and n i = ∣ Γ i ∣ n_{i} = \left| \Gamma_{i} \right| n i = ∣ Γ i ∣ , let the standard basis corresponding to C Γ i \mathbb{C}^{\Gamma_{i}} C Γ i be denoted as { e j i } j i ∈ Γ i \left\{ e_{j_{i}} \right\}_{j_{i} \in \Gamma_{i}} { e j i } j i ∈ Γ i respectively. Then, v i v_{i} v i can be represented as follows.
v 1 : { 1 , … , n 1 } → C v 2 : { 1 , … , n 2 } → C v 1 = ( v 1 ( 1 ) , … , v 1 ( n 1 ) ) ∈ C n 1 v 2 = ( v 2 ( 1 ) , … , v 2 ( n 2 ) ) ∈ C n 2 = ∑ j 1 = 1 n 1 v 1 ( j 1 ) e j 1 = ∑ j 2 = 1 n 2 v 2 ( j 2 ) e j 2
\begin{align*}
v_{1} &: \left\{ 1, \dots, n_{1} \right\} \to \mathbb{C} &&& v_{2} &: \left\{ 1, \dots, n_{2} \right\} \to \mathbb{C} \\
v_{1} &= (v_{1}(1), \dots, v_{1}(n_{1})) \in \mathbb{C}^{n_{1}} &&& v_{2} &= (v_{2}(1), \dots, v_{2}(n_{2})) \in \mathbb{C}^{n_{2}} \\
& = \sum \limits_{j_{1} = 1}^{n_{1}}v_{1}(j_{1}) e_{j_{1}} &&&& = \sum \limits_{j_{2} = 1}^{n_{2}}v_{2}(j_{2}) e_{j_{2}}
\end{align*}
v 1 v 1 : { 1 , … , n 1 } → C = ( v 1 ( 1 ) , … , v 1 ( n 1 )) ∈ C n 1 = j 1 = 1 ∑ n 1 v 1 ( j 1 ) e j 1 v 2 v 2 : { 1 , … , n 2 } → C = ( v 2 ( 1 ) , … , v 2 ( n 2 )) ∈ C n 2 = j 2 = 1 ∑ n 2 v 2 ( j 2 ) e j 2
The elements of the tensor product C Γ 1 ⊗ C Γ 2 \mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}} C Γ 1 ⊗ C Γ 2 that can be represented as v 1 ⊗ v 2 v_{1} \otimes v_{2} v 1 ⊗ v 2 are called the product vector of v 1 v_{1} v 1 and v 2 v_{2} v 2 .
Definition The product vector v 1 ⊗ v 2 v_{1} \otimes v_{2} v 1 ⊗ v 2 of v 1 v_{1} v 1 and v 2 v_{2} v 2 is defined as follows.
v 1 ⊗ v 2 = ( ∑ j 1 ∈ Γ 1 v 1 ( j 1 ) e j 1 ) ⊗ ( ∑ j 2 ∈ Γ 2 v 2 ( j 2 ) e j 2 ) : = ∑ ( j 1 , j 2 ) ∈ Γ 1 × Γ 2 ( ∏ i = 1 2 v i ( j i ) ) e j 1 ⊗ e j 2
\begin{align*}
v_{1} \otimes v_{2} &= \left( \sum \limits_{j_{1} \in \Gamma_{1}}v_{1}(j_{1}) e_{j_{1}} \right) \otimes \left( \sum \limits_{j_{2} \in \Gamma_{2}}v_{2}(j_{2}) e_{j_{2}} \right) \\
&:= \sum\limits_{(j_{1}, j_{2}) \in \Gamma_{1} \times \Gamma_{2}} \left( \prod\limits_{i=1}^{2} v_{i}(j_{i}) \right) e_{j_{1}} \otimes e_{j_{2}}
\end{align*}
v 1 ⊗ v 2 = j 1 ∈ Γ 1 ∑ v 1 ( j 1 ) e j 1 ⊗ j 2 ∈ Γ 2 ∑ v 2 ( j 2 ) e j 2 := ( j 1 , j 2 ) ∈ Γ 1 × Γ 2 ∑ ( i = 1 ∏ 2 v i ( j i ) ) e j 1 ⊗ e j 2
In this case, v 1 ⊗ v 2 v_{1} \otimes v_{2} v 1 ⊗ v 2 becomes an element of C Γ 1 ⊗ C Γ 2 \mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}} C Γ 1 ⊗ C Γ 2 by the definition of the tensor product.
v 1 ⊗ v 2 : = ∑ ( j 1 , j 2 ) ∈ Γ 1 × Γ 2 ( ∏ i = 1 2 v i ( j i ) ) e j 1 ⊗ e j 2 ∈ C Γ 1 ⊗ C Γ 2
v_{1} \otimes v_{2} := \sum\limits_{(j_{1}, j_{2}) \in \Gamma_{1} \times \Gamma_{2}} \left( \prod\limits_{i=1}^{2} v_{i}(j_{i}) \right) e_{j_{1}} \otimes e_{j_{2}} \in \mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}}
v 1 ⊗ v 2 := ( j 1 , j 2 ) ∈ Γ 1 × Γ 2 ∑ ( i = 1 ∏ 2 v i ( j i ) ) e j 1 ⊗ e j 2 ∈ C Γ 1 ⊗ C Γ 2
Explanation Not all elements of C Γ 1 ⊗ C Γ 2 \mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}} C Γ 1 ⊗ C Γ 2 can be represented as the product vector form of v 1 ⊗ v 2 v_{1} \otimes v_{2} v 1 ⊗ v 2 . For example, the following vector can be expressed as the product of two vectors, but ( e 1 ⊗ e 1 ) + ( e 2 ⊗ e 2 ) (e_{1} \otimes e_{1}) + (e_{2} \otimes e_{2}) ( e 1 ⊗ e 1 ) + ( e 2 ⊗ e 2 ) cannot.
e 1 ⊗ e 1 − e 1 ⊗ e 2 + e 2 ⊗ e 1 − e 2 ⊗ e 2 = ( e 1 + e 2 ) ⊗ ( e 1 − e 2 )
e_{1} \otimes e_{1} - e_{1} \otimes e_{2} + e_{2} \otimes e_{1} - e_{2} \otimes e_{2} = (e_{1} + e_{2}) \otimes (e_{1} - e_{2})
e 1 ⊗ e 1 − e 1 ⊗ e 2 + e 2 ⊗ e 1 − e 2 ⊗ e 2 = ( e 1 + e 2 ) ⊗ ( e 1 − e 2 )
As a simple example, let’s further unpack the definition above. Let’s say Γ 1 = { 1 , 2 } \Gamma_{1} = \left\{ 1, 2 \right\} Γ 1 = { 1 , 2 } , Γ 2 = { 1 , 2 , 3 } \Gamma_{2} = \left\{ 1, 2, 3 \right\} Γ 2 = { 1 , 2 , 3 } . Assume v i ∈ C Γ i v_{i} \in \mathbb{C}^{\Gamma_{i}} v i ∈ C Γ i . Let the standard basis corresponding to C Γ 1 = C 2 \mathbb{C}^{\Gamma_{1}} = \mathbb{C}^{2} C Γ 1 = C 2 be { e j 1 } j 1 ∈ Γ 1 \left\{ e_{j_{1}} \right\}_{j_{1} \in \Gamma_{1}} { e j 1 } j 1 ∈ Γ 1 , and the standard basis corresponding to C Γ 2 = C 3 \mathbb{C}^{\Gamma_{2}} = \mathbb{C}^{3} C Γ 2 = C 3 be { e j 2 } j 2 ∈ Γ 2 \left\{ e_{j_{2}} \right\}_{j_{2} \in \Gamma_{2}} { e j 2 } j 2 ∈ Γ 2 . Then, v 1 v_{1} v 1 , v 2 v_{2} v 2 are as follows.
v 1 : { 1 , 2 } → C v 2 : { 1 , 2 , 3 } → C v 1 = ( v 1 ( 1 ) , v 1 ( 2 ) ) ∈ C 2 v 2 = ( v 2 ( 1 ) , v 2 ( 2 ) , v 2 ( 3 ) ) ∈ C 3 = ∑ j 1 = 1 2 v 1 ( j 1 ) e j 1 = ∑ j 2 = 1 3 v 2 ( j 2 ) e j 2
\begin{align*}
v_{1} &: \left\{ 1, 2 \right\} \to \mathbb{C} &&& v_{2} &: \left\{ 1, 2, 3 \right\} \to \mathbb{C} \\
v_{1} &= (v_{1}(1), v_{1}(2)) \in \mathbb{C}^{2} &&& v_{2} &= (v_{2}(1), v_{2}(2), v_{2}(3)) \in \mathbb{C}^{3} \\
& = \sum \limits_{j_{1} = 1}^{2}v_{1}(j_{1}) e_{j_{1}} &&&& = \sum \limits_{j_{2} = 1}^{3}v_{2}(j_{2}) e_{j_{2}}
\end{align*}
v 1 v 1 : { 1 , 2 } → C = ( v 1 ( 1 ) , v 1 ( 2 )) ∈ C 2 = j 1 = 1 ∑ 2 v 1 ( j 1 ) e j 1 v 2 v 2 : { 1 , 2 , 3 } → C = ( v 2 ( 1 ) , v 2 ( 2 ) , v 2 ( 3 )) ∈ C 3 = j 2 = 1 ∑ 3 v 2 ( j 2 ) e j 2
Then, the product vector of v 1 v_{1} v 1 and v 2 v_{2} v 2 is as follows.
v 1 ⊗ v 2 = ( v 1 ( 1 ) , v 1 ( 2 ) ) ⊗ ( v 2 ( 1 ) , v 2 ( 2 ) , v 2 ( 3 ) ) = ( ∑ j 1 = 1 2 v 1 ( j 1 ) e j 1 ) ⊗ ( ∑ j 2 = 1 3 v 2 ( j 2 ) e j 2 ) : = ∑ ( j 1 , j 2 ) ∈ Γ 1 × Γ 2 ( ∏ i = 1 2 v i ( j i ) ) e j 1 ⊗ e j 2 ∈ C Γ 1 ⊗ C Γ 2 = v 1 ( 1 ) v 2 ( 1 ) e 1 ⊗ e 1 + v 1 ( 1 ) v 2 ( 2 ) e 1 ⊗ e 2 + v 1 ( 1 ) v 2 ( 3 ) e 1 ⊗ e 3 + v 1 ( 2 ) v 2 ( 1 ) e 1 ⊗ e 1 + v 1 ( 2 ) v 2 ( 2 ) e 1 ⊗ e 2 + v 1 ( 2 ) v 2 ( 3 ) e 1 ⊗ e 3 = ( v 1 ( 1 ) v 2 ( 1 ) , v 1 ( 1 ) v 2 ( 2 ) , v 1 ( 1 ) v 2 ( 3 ) , v 1 ( 2 ) v 2 ( 1 ) , v 1 ( 2 ) v 2 ( 2 ) , v 1 ( 2 ) v 2 ( 3 ) ) ∈ C 6 ≅ C Γ 1 ⊗ C Γ 2
\begin{align*}
v_{1} \otimes v_{2}
&= (v_{1}(1), v_{1}(2)) \otimes (v_{2}(1), v_{2}(2), v_{2}(3)) \\
&= \left( \sum \limits_{j_{1} = 1}^{2} v_{1}(j_{1}) e_{j_{1}} \right) \otimes \left( \sum \limits_{j_{2} = 1}^{3} v_{2}(j_{2}) e_{j_{2}} \right) \\
&:= \sum\limits_{(j_{1}, j_{2}) \in \Gamma_{1} \times \Gamma_{2}} \left( \prod\limits_{i=1}^{2} v_{i}(j_{i}) \right) e_{j_{1}} \otimes e_{j_{2}} \in \mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}} \\
&= v_{1}(1)v_{2}(1)e_{1} \otimes e_{1} + v_{1}(1)v_{2}(2)e_{1} \otimes e_{2} + v_{1}(1)v_{2}(3)e_{1} \otimes e_{3} \\
&\quad + v_{1}(2)v_{2}(1)e_{1} \otimes e_{1} + v_{1}(2)v_{2}(2)e_{1} \otimes e_{2} + v_{1}(2)v_{2}(3)e_{1} \otimes e_{3} \\
&= \left( v_{1}(1)v_{2}(1), v_{1}(1)v_{2}(2), v_{1}(1)v_{2}(3), v_{1}(2)v_{2}(1), v_{1}(2)v_{2}(2), v_{1}(2)v_{2}(3) \right) \\
&\in \mathbb{C}^{6} \cong \mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}}
\end{align*}
v 1 ⊗ v 2 = ( v 1 ( 1 ) , v 1 ( 2 )) ⊗ ( v 2 ( 1 ) , v 2 ( 2 ) , v 2 ( 3 )) = ( j 1 = 1 ∑ 2 v 1 ( j 1 ) e j 1 ) ⊗ ( j 2 = 1 ∑ 3 v 2 ( j 2 ) e j 2 ) := ( j 1 , j 2 ) ∈ Γ 1 × Γ 2 ∑ ( i = 1 ∏ 2 v i ( j i ) ) e j 1 ⊗ e j 2 ∈ C Γ 1 ⊗ C Γ 2 = v 1 ( 1 ) v 2 ( 1 ) e 1 ⊗ e 1 + v 1 ( 1 ) v 2 ( 2 ) e 1 ⊗ e 2 + v 1 ( 1 ) v 2 ( 3 ) e 1 ⊗ e 3 + v 1 ( 2 ) v 2 ( 1 ) e 1 ⊗ e 1 + v 1 ( 2 ) v 2 ( 2 ) e 1 ⊗ e 2 + v 1 ( 2 ) v 2 ( 3 ) e 1 ⊗ e 3 = ( v 1 ( 1 ) v 2 ( 1 ) , v 1 ( 1 ) v 2 ( 2 ) , v 1 ( 1 ) v 2 ( 3 ) , v 1 ( 2 ) v 2 ( 1 ) , v 1 ( 2 ) v 2 ( 2 ) , v 1 ( 2 ) v 2 ( 3 ) ) ∈ C 6 ≅ C Γ 1 ⊗ C Γ 2
By carefully observing the components of v 1 ⊗ v 2 v_{1} \otimes v_{2} v 1 ⊗ v 2 , one could guess its relation to matrices.
Coordinate Matrix Consider the matrix space M m × n ( C ) M_{m \times n}(\mathbb{C}) M m × n ( C ) . If E i j E_{ij} E ij has components ( i , j ) (i,j) ( i , j ) as 1 1 1 and the rest as 0 0 0 , it is called an m × n m \times n m × n matrix, and { E i j } \left\{ E_{ij} \right\} { E ij } becomes the basis of M m × n ( C ) M_{m\times n}(\mathbb{C}) M m × n ( C ) . Let ϕ \phi ϕ be a linear transformation that maps the basis vector e i ⊗ e j e_{i} \otimes e_{j} e i ⊗ e j of the tensor product C m ⊗ C n \mathbb{C}^{m} \otimes \mathbb{C}^{n} C m ⊗ C n to E i j E_{ij} E ij .
ϕ : C m ⊗ C n → M m × n ( C ) e i ⊗ e j ↦ E i j
\begin{align*}
\phi : \mathbb{C}^{m} \otimes \mathbb{C}^{n} &\to M_{m \times n} (\mathbb{C}) \\
e_{i} \otimes e_{j} &\mapsto E_{ij}
\end{align*}
ϕ : C m ⊗ C n e i ⊗ e j → M m × n ( C ) ↦ E ij
Since it maps a basis to a basis, it becomes an isomorphism . If two vectors v ∈ C m v \in \mathbb{C}^{m} v ∈ C m , w ∈ C n w \in \mathbb{C}^{n} w ∈ C n are as follows,
v = ∑ i α i e i = [ α 1 ⋮ α m ] w = ∑ j β j e j = [ β 1 ⋮ β n ]
v = \sum_{i} \alpha_{i}e_{i} = \begin{bmatrix} \alpha_{1} \\ \vdots \\ \alpha_{m} \end{bmatrix} \qquad
w = \sum_{j} \beta_{j}e_{j} = \begin{bmatrix} \beta_{1} \\ \vdots \\ \beta_{n} \end{bmatrix}
v = i ∑ α i e i = α 1 ⋮ α m w = j ∑ β j e j = β 1 ⋮ β n
Sending the product vector v , w v, w v , w through ϕ \phi ϕ results in the following.
ϕ ( v ⊗ w ) = ϕ ( ∑ i , j α i β j e i ⊗ e j ) = ∑ i , j α i β j ϕ ( e i ⊗ e j ) = ∑ i , j α i β j E i j = [ α 1 β 1 ⋯ α 1 β n ⋮ ⋱ ⋮ α m β 1 ⋯ α m β n ] = [ α 1 ⋮ α m ] [ β 1 ⋯ β n ] = v w T
\begin{align*}
\phi ( v \otimes w )
&= \phi \left( \sum\limits_{i,j} \alpha_{i}\beta_{j} e_{i} \otimes e_{j} \right) \\
&= \sum\limits_{i,j} \alpha_{i}\beta_{j} \phi \left( e_{i} \otimes e_{j} \right) \\
&= \sum\limits_{i,j} \alpha_{i}\beta_{j} E_{ij} \\
&= \begin{bmatrix}
\alpha_{1}\beta_{1} & \cdots & \alpha_{1}\beta_{n} \\
\vdots & \ddots & \vdots \\
\alpha_{m}\beta_{1} & \cdots & \alpha_{m}\beta_{n} \\
\end{bmatrix} \\
&= \begin{bmatrix} \alpha_{1} \\ \vdots \\ \alpha_{m} \end{bmatrix}
\begin{bmatrix} \beta_{1} & \cdots & \beta_{n} \end{bmatrix} \\
&= vw^{T}
\end{align*}
ϕ ( v ⊗ w ) = ϕ ( i , j ∑ α i β j e i ⊗ e j ) = i , j ∑ α i β j ϕ ( e i ⊗ e j ) = i , j ∑ α i β j E ij = α 1 β 1 ⋮ α m β 1 ⋯ ⋱ ⋯ α 1 β n ⋮ α m β n = α 1 ⋮ α m [ β 1 ⋯ β n ] = v w T
This corresponds to a matrix whose elements are α i β j \alpha_{i}\beta_{j} α i β j . Therefore, by ϕ \phi ϕ , the product vector v ⊗ w v \otimes w v ⊗ w corresponds to a single m × n m \times n m × n . The matrix ϕ ( v ⊗ w ) = v w T \phi (v \otimes w) = vw^{T} ϕ ( v ⊗ w ) = v w T is called the coordinate matrix of v ⊗ w v \otimes w v ⊗ w with respect to the standard basis. This concept can be seen as analogous to a vector’s coordinate vector .
Generalization For finite sets Γ i ( 1 ≤ i ≤ r ) \Gamma_{i} (1 \le i \le r) Γ i ( 1 ≤ i ≤ r ) , Γ = Γ 1 × ⋯ × Γ r \Gamma = \Gamma_{1} \times \cdots \times \Gamma_{r} Γ = Γ 1 × ⋯ × Γ r , v i ∈ C Γ i v_{i} \in \mathbb{C}^{\Gamma_{i}} v i ∈ C Γ i , the product vectors of v i v_{i} v i are defined as follows.
v 1 ⊗ ⋯ ⊗ v r = ( ∑ j 1 ∈ Γ 1 v 1 ( j 1 ) e j 1 ) ⊗ ⋯ ⊗ ( ∑ j r ∈ Γ r v r ( j r ) e j r ) : = ∑ ( j 1 , … , j r ) ∈ Γ ( ∏ i = 1 r v i ( j i ) ) e j 1 ⊗ ⋯ ⊗ e j r = ∈ C Γ 1 ⊗ ⋯ ⊗ C Γ r
\begin{align*}
v_{1} \otimes \cdots \otimes v_{r} &= \left( \sum \limits_{j_{1} \in \Gamma_{1}}v_{1}(j_{1}) e_{j_{1}} \right) \otimes \cdots \otimes \left( \sum \limits_{j_{r} \in \Gamma_{r}}v_{r}(j_{r}) e_{j_{r}} \right) \\
&:= \sum\limits_{(j_{1}, \dots, j_{r}) \in \Gamma} \left( \prod\limits_{i=1}^{r} v_{i}(j_{i}) \right) e_{j_{1}} \otimes \cdots \otimes e_{j_{r}} \\
&= \in \mathbb{C}^{\Gamma_{1}} \otimes \cdots \otimes \mathbb{C}^{\Gamma_{r}}
\end{align*}
v 1 ⊗ ⋯ ⊗ v r = j 1 ∈ Γ 1 ∑ v 1 ( j 1 ) e j 1 ⊗ ⋯ ⊗ j r ∈ Γ r ∑ v r ( j r ) e j r := ( j 1 , … , j r ) ∈ Γ ∑ ( i = 1 ∏ r v i ( j i ) ) e j 1 ⊗ ⋯ ⊗ e j r =∈ C Γ 1 ⊗ ⋯ ⊗ C Γ r
See Also